(untitled) (Research, Society and Development, 2021)
The objective this article is identify the cognitive response possible pattern associated the estrogen and/or progesterone supplementation in postmenopausal women. Was carried a systematic literature review using the PRISMA protocol and quantitative-qualitative analysis in the PubMed and Scientific Electronic Library Online (SCIELO) databases using the Health Sciences Descriptors (DeCS) “Cognition” and “Hormone replacement therapy” in English and synonyms. Were identified 349 articles and after apply the filters were resulted 82 publications. There was no duplication between the surveyed databases. After excluding animal studies, literature reviews and articles that Hormone Replacement Therapy was used for purposes other than the treatment of menopausal symptoms, there were still 09 articles to be analyzed. The hormone therapy negatively influenced in orientation, abstract reasoning, brain volume and questions, also exacerbating the negative effects of Diabetes Mellitus on cognition. However, in the domains attention, processing speed, working and verbal memory was a positive influence, showing that women who used hormone therapy performed better than those who never used it. In view of the conflicting results, further studies are needed to assess the influence of different formulations, in addition, the risk factors for cognitive decline should be taken into account when indicating hormonal therapy, because even if the treatment does not is indicated for cognitive purposes, its decline can have a great impact on women’s quality of life.